Early discharge after acute myocardial infarction: risks and benefits. Issue 1 (July 1995) - Wilkinson, P.; Stevenson, R.; Ranjadayalan, K.; Marchant, B.; Roberts, R.; Timmis, A. D.
Abstract : BACKGROUND–Thrombolytic treatment reduces mortality in patients with acute myocardial infarction but is associated with recurrent thrombotic events after admission, and it is unclear whether current practices of early hospital discharge are safe. Timing of first major adverse events (death, reinfarction, unstable angina, secondary ventricular fibrillation) in the early post-infarction period was studied to determine the risks. DESIGN–Follow up study. PATIENTS–608 consecutive patients (447 men and 161 women) with confirmed myocardial infarction who were admitted to the coronary care unit of a district general hospital between January 1989 and December 1991. Clinical details, including the development of left ventricular failure and in hospital adverse events, were recorded prospectively. Follow up for out of hospital adverse events was carried out by review of the case notes, postal questionnaire, and where necessary, by telephone contact with the patient and his general practitioner. RESULTS–The risk (95% confidence interval) of major adverse events in the first 10 days was 32.3% (26.3 to 39.4%) in patients with heart failure and 7.3% (5.1 to 9.2%) in those without. Smoothed estimates of the event rate in patients without heart failure decreased from 5.9 events/1000 persons/day on day 6 to 3.4 events/1000 persons/day on day 10 and 0.9 events/1000 persons/day on day 21. The corresponding cumulative risk estimates suggest that about 11 in every 1000 patients suffer a major, but often unpreventable, adverse event on day 6 or 7 after admission, and 23 in every 1000 do so between days 6 and 10. CONCLUSIONS–The point at which the risk to the individual becomes acceptably low is a matter of judgement, but the risk of a major adverse event declines rapidly after a heart attack, and particularly for patients without heart failure discharge within a few days may be appropriate. Prolonging stay unnecessarily may use resources which could be more effectively used to treat cardiac disease in other ways.